(7y+4)-(2+6y)=5

Simple and best practice solution for (7y+4)-(2+6y)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7y+4)-(2+6y)=5 equation:


Simplifying
(7y + 4) + -1(2 + 6y) = 5

Reorder the terms:
(4 + 7y) + -1(2 + 6y) = 5

Remove parenthesis around (4 + 7y)
4 + 7y + -1(2 + 6y) = 5
4 + 7y + (2 * -1 + 6y * -1) = 5
4 + 7y + (-2 + -6y) = 5

Reorder the terms:
4 + -2 + 7y + -6y = 5

Combine like terms: 4 + -2 = 2
2 + 7y + -6y = 5

Combine like terms: 7y + -6y = 1y
2 + 1y = 5

Solving
2 + 1y = 5

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 1y = 5 + -2

Combine like terms: 2 + -2 = 0
0 + 1y = 5 + -2
1y = 5 + -2

Combine like terms: 5 + -2 = 3
1y = 3

Divide each side by '1'.
y = 3

Simplifying
y = 3

See similar equations:

| 7(x-6)+4=3x-6 | | Z^8=1 | | 5(3x-1/5(-2))=10 | | Z^9=i | | 2x(x-1)-7x=18-5(x+4) | | 21=5x+7y | | 12x(x+2)=0 | | (2x/2)=7x-1 | | 4(5x-3)+2=30 | | 6=j-88 | | X+21+2x=-12-2x-17 | | (2n-4)(3n-6)=0 | | y-1.1=-1.2 | | 10=f/3 | | x+20=43 | | X+21+2x=12-2x-17 | | 20/x-5=-8/6 | | 3+10=s | | -9a=72 | | .09x=5 | | 4y+u+35=180 | | 12x+5=-2x+19 | | .09x=10 | | 2/9v=14 | | .09x=15 | | -x^3+1.5x^2-.5x=0 | | -x^3+1.5x^2-04x=0 | | 3+10=5 | | A=(1/2)bb | | 2cos^2(x)+9cos(x)=0 | | 3y+8=2y-8 | | -3x+9=3+4x+(-7x)+6 |

Equations solver categories